The Brazilian Conservative Wave, the Bolsonaro Administration, and Religious Actors - Joanildo Burity (Brazilian Political Science Review, 2021)
Despite the obvious connection between conservative Christian leaders and Bolsonaro, from his electoral campaign to the formation of his administration, religious agency in Brazilian politics goes beyond a mere conservative register. This article seeks to trace various dimensions of the trajectory made by evangelicals in Brazilian politics as a tipping factor in the emergence of a new protagonism of religious actors in politics. It discusses how the emergence of evangelicals as public actors has included different ideological and practical expressions, as well as internal disputes and ventures some remarks on whither current trends point to as Bolsonaro’s government makes room for the evangelical right but sparks reactions and rearticulations from various forms of evangelical progressives.